Prevalence of the crayfish plague pathogen in red swamp crayfish populations in western France: How serious is the risk for the native white-clawed crayfish? - Laffitte, Maud; Mojžišová, Michaela; Delaunay, Carine; Collas, Marc; Petrusek, Adam; Grandjean, Frederic (Journal of invertebrate pathology, 2024)
The crayfish plague pathogen Aphanomyces astaci has been implicated in a number of mass mortalities and irreversible population declines of native crayfish across Europe. At present, the reservoirs of the pathogen in Europe are mainly populations of invasive North American crayfish species. In southwestern Europe, including France, a particularly widespread invader is the red swamp crayfish Procambarus clarkii. Recent distribution data confirm that P. clarkii is present in at least 75 French departments, i.e. more than 78% of those in metropolitan France. We analysed the prevalence and pathogen load of A. astaci in 42 populations of this species in western France (Nouvelle Aquitaine region), where the species is most densely distributed, particularly in a wide range of environments around the Gironde estuary. The pathogen was detected by two different quantitative PCR assays in more than three quarters of the populations studied (34 out of 42); 163 out of 480 analysed crayfish individuals tested positive for the presence of A. astaci. In most cases, individual infection levels were very low, detectable with quantitative PCR but not sufficient for pathogen genotyping. In seven P. clarkii individuals from four populations, however, we were able to assess A. astaci variation by microsatellite markers and sequencing of mitochondrial markers. All these host specimens carried A. astaci genotype group D, haplotype d1, which has caused the majority of crayfish plague outbreaks in neighbouring Spain. In contrast, the French outbreaks genotyped to date (including eight newly analysed in this study) were mostly caused by strains of genotype group B, specific to the signal crayfish Pacifastacus leniusculus. Haplotype d1 found in P. clarkii was involved in one of the newly characterised outbreaks. Our study confirms that P. clarkii is a potentially important reservoir of the crayfish plague pathogen in France, but not the main source of the pathogen in mass mortalities of A. pallipes, probably due to different ecological requirements of the different invasive host crayfish. However, as P. clarkii continues to spread, the threat posed by this species to native crayfish is likely to increase.
Keywords: Astacoidea; Mass mortality; Animals; France; Invasive crayfish distribution; Crayfish plague; prevalence; Pathogen transmission; Procambarus clarkii; zvířata; Prevalence; Introduced Species; Francie; severní raci; zavlečené druhy; Aphanomyces astaci; Aphanomyces